213k views
5 votes
If C(x) = 4x^2 - 3, find the following

(a) C(0)
(b) C (-1)
(c) C (-2)
(d) C (-3/2)

If C(x) = 4x^2 - 3, find the following (a) C(0) (b) C (-1) (c) C (-2) (d) C (-3/2)-example-1
User AshD
by
5.4k points

1 Answer

1 vote

Explanation:


C(x)=4x^2-3\\\\C(0),\ C(-1),\ C(-2),\ C\left(-(3)/(2)\right)\\\\\text{Substitute each value}\ \left\{0, -1, -2, -(3)/(2)\right\}\ \text{instead}\ C(x):\\\\C(0)=4(0^2)-3=4(0)-3=0-3=-3\\\\C(-1)=4(-1)^2-3=4(1)-3=4-3=1\\\\C(-2)=4(-2)^2-3=4(4)-3=16-3=13\\\\C\left(-(3)/(2)\right)=4\left(-(3)/(2)\right)^2-3=4\left((9)/(4)\right)-3=9-3=6

User Nelo Mitranim
by
5.9k points